Biological variation and device error in vertical jump height with two types of measurement system - Lipinska, P.; Pueo, B.; Jimenez-Olmedo, J. M.; Penichet-Tomás, A.; Mijewski, P.; Hopkins, W. G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Vertical-jump tests are used to evaluate lower-body power of athletes and non-athletes. The aim of this study was to compare two methodologies for such tests: the popular and convenient jump mat, and a criterion method, motion capture by video analysis. Methods: Thirty-one young adult males (15 rowers and 19 non-athletes) alternated four countermovement jumps (CMJ) with four standing jumps (SJ). Jump height was measured with a commercially available jump mat and simultaneously by video. The modifying effects of foot length on the two measures of jump height were estimated with a mixed model, which also allowed separate estimation of errors arising from the subject and from the device. Effects were evaluated using standardization and non-clinical magnitude-based inference. Results: Countermovement jump height was 34.4 ± 6.2 cm and 47.8 ± 6.8 cm for the jump mat and video respectively (mean ± SD). Foot length had a clearly positive small effect on jump height for the video compared with the jump mat (1.8 ±0.6 cm per 3 cm of foot length for CMJ, mean ±90% confidence limits; similar effect for SJ). Adjustment to zero foot length removed most of the difference in jump height between the methods, although the remaining difference was unclear. Within-subject variability for CMJ and SJ were both 1.5 cm (SD, 90% confidence limits ±0.2 cm). Device errors with jump mat and video were similar for CMJ (SD 0.7 and 0.8 cm respectively), but less with the jump mat for SJ (SD 0.2 and 0.8 cm respectively). Discussion: The substantial difference between jump height with the jump mat and video can be explained by the effect of foot length on the way flight time is recorded on the jump mat. Both methods contributed a similar substantial amount of error for countermovement jumps, but surprisingly, the jump mat had less error for standing jumps. We conclude that a jump mat provides trustworthy measurements for monitoring changes in jump height.